Importance Of Soil Solution in The Growth and Development of Soybean (Glycine Max L.) (American Scholar: Journal of Interdisciplinary Research and Knowledge, 2026)
Soybean (Glycine max L.) is one of the most important leguminous crops worldwide due to its high protein and oil content. The growth, development, and productivity of soybean largely depend on soil fertility and the availability of nutrients in the soil solution. Soil solution serves as the primary medium through which plants absorb water and essential mineral nutrients. This article examines the significance of soil solution in soybean growth, nutrient uptake, physiological processes, root development, biological nitrogen fixation, and crop productivity. The study highlights the relationship between soil solution composition, nutrient availability, soil pH, and soybean yield. Maintaining an optimal soil solution environment through proper fertilization, irrigation, and soil management practices is essential for achieving sustainable soybean production.
Keywords: Soybean; Soil Solution; Nutrient Uptake; Rhizosphere